2010
DOI: 10.4103/0975-9476.65073
|View full text |Cite
|
Sign up to set email alerts
|

Bioenhancers: Revolutionary concept to market

Abstract: Treatment cost is a major concern for modern medicine in developing countries like India and systematic innovative means to reduce these costs are needed. This article reviews the concept of bioenhancers to reduce treatment costs by increasing drug bioavailability. This concept, based on the Ayurvedic system of medicine, works for a wide range of ingested substances, and has been applied to modern drugs, particularly single chemicals. It offers a fine example of the benefit of integrating an ancient system wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 9 publications
2
64
1
Order By: Relevance
“…Ginger is known to enhance the bioavailability by regulating the GIT function [20]. Although there are reports which indicate that use of ginger extract enhances the bioavailability of many drugs [21][22][23], we did not get satisfactory results , which is suggestive that bioenhancers working on the gut motility may not be the right candidates to be studied by this method. It may also be possible that the ginger extract might be forming a coating over the mucosal surface thereby hindering the absorption of Amoxicillin trihydrate.…”
Section: In Vitro Studies Using Non Everted Gut Sac Methodscontrasting
confidence: 53%
“…Ginger is known to enhance the bioavailability by regulating the GIT function [20]. Although there are reports which indicate that use of ginger extract enhances the bioavailability of many drugs [21][22][23], we did not get satisfactory results , which is suggestive that bioenhancers working on the gut motility may not be the right candidates to be studied by this method. It may also be possible that the ginger extract might be forming a coating over the mucosal surface thereby hindering the absorption of Amoxicillin trihydrate.…”
Section: In Vitro Studies Using Non Everted Gut Sac Methodscontrasting
confidence: 53%
“…However in general, this type of release profile potentially can cross the toxic drug-concentration level within initial hours and sub therapeutic drug concentration in later part [23]. As piperine is the most formidable bio-enhancer till date, it helps to enhance the bio-availability of other drugs by boosting the absorption from the intestine [24]. It also has anti-microbial, anti-inflammatory, anti-depressant, anticancerous effects [25][26][27] apart from being hydrophobic in nature.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Sometimes, this type of positive pharmacokinetic interactions beyond certain degree are deliberately used to improve the exposure of drugs that also eventually beneficial for poor bioavailable drugs or drugs having dose dependent side effects to reduce dose. 8 Common mechanisms of curcumin for pharmacokinetic interactions as evidenced from literature are modulated through down regulation of CYP450, followed by P-gp and a few downstream pathways involving OATP, glutathione-S-transferase (GST) and uridine dinucleotide phosphate glucuronosyltransferases (UDPG). Based on in-vitro studies reported data, curcumin could inhibit P-gp in dose dependent manner at micromolar concentration range and inhibit CYP3A4 competitively with low potency of more than 10 ÎŒM.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, dose of curcumin (2.5/5/10 mg/kg) was on the basis of bioenhancer mechanism which function at low doses. 8 Individual dose was prepared as solution form using 10% DMSO, 20% solutol HS15 and water (q.s) for oral administration of curcumin and daclatasvir dihydrochloride.…”
Section: Dose Selection and Preparationmentioning
confidence: 99%